Performance characterization for noisy quantum technologies - Liuzzo Scorpo, Pietro (2018)
The fast development of quantum technologies requires a new theoretical effort to characterize their performance in practical scenarios. By studying both discrete and continuous variable systems, we will explore several research lines, such as control theory, quantum metrology and non-Markovianity. The thread connecting these different fields will be an approach that attempts to determine the limits and the potentiality of quantum performance in the presence of noise and scarcity of resources. Indeed, the goal of this thesis is to investigate whether quantum features can enhance the performance of particular instances of quantum protocols, and, if this is the case, how this enhancement is affected when some restrictions on the practical implementation of these protocols are in place.